Bighorn sheep show similar in‐host responses to the same pathogen strain in two contrasting environments. Issue 7 (17th July 2022) - Manlove, Kezia R.; Roug, Annette; Sinclair, Kylie; Ricci, Lauren E.; Hersey, Kent R.; Martinez, Cameron; Martinez, Michael A.; Mower, Kerry; Ortega, Talisa; Rominger, Eric; Ruhl, Caitlin; Tatman, Nicole; et al.
Abstract: Ecological context—the biotic and abiotic environment, along with its influence on population mixing dynamics and individual susceptibility—is thought to have major bearing on epidemic outcomes. However, direct comparisons of wildlife disease events in contrasting ecological contexts are often confounded by concurrent differences in host genetics, exposure histories, or pathogen strains. Here, we compare disease dynamics of a Mycoplasma ovipneumoniae spillover event that affected bighorn sheep populations in two contrasting ecological contexts. One event occurred on the herd's home range near the Rio Grande Gorge in New Mexico, while the other occurred in a captive facility at Hardware Ranch in Utah. While data collection regimens varied, general patterns of antibody signal strength and symptom emergence were conserved between the two sites. Symptoms appeared in the captive setting an average of 12.9 days postexposure, average time to seroconversion was 24.9 days, and clinical signs peaked at approximately 36 days postinfection. These patterns were consistent with serological testing and subsequent declines in symptom intensity in the free‐ranging herd. At the captive site, older animals exhibited more severe declines in body condition and loin thickness, higher symptom burdens, and slower antibody response to the pathogen than younger animals. Younger animals were more likely than older animals to clear infection by the time of sampling at both sites. The patterns presented here suggest that environment may not be a major determinant of epidemiological outcomes in the bighorn sheep— M. ovipneumoniae system, elevating the possibility that host‐ or pathogen‐factors may be responsible for observed variation. Abstract : In this Nature Note, we compare disease dynamics of the same Mycoplasma ovipneumoniae strain in captive and free‐ranging bighorn sheep, and find strong parallels between dynamics in the two environments. The similarity in patterns across the two sites suggests that environmental factors may be less important that pathogen strain or host factors like genetics in producing variable outcomes among different bighorn sheep Mycoplasma ovipneumoniae disease events.